Party System Institutionalization Without Parties: Evidence from Korea. (April 2014) - Hellmann, Olli
Abstract : Formally institutionalized party organization is usually considered a prerequisite for the development of programmatic linkages between parties and voters. However, in this article I show that political parties in South Korea have succeeded in stabilizing interparty competition through programmatic linkages without making any significant efforts to build a formal organizational base. In fact, it could be argued that South Korea is a "partyless" democracy, as political parties get easily captured by the interests of ambitious politicians, thus failing to establish themselves as independent actors. I therefore make a more general argument about the concept of party system institutionalization: we need to rethink the current practice of aggregating the different attributes of party system institutionalization into a single scale, as these attributes do not seem to be connected in a linear fashion.